How does the audit committee affect ESG performance? A case of China - Le, Dung Quang; Ngoc, Quy Nguyen; Do, Tra My Nguyen; Hong, Nhung Luong; Ngoc, Minh Anh Vu (Asian Economic and Financial Review, 2025)
This study aims to investigate the impact of Audit Committee (AC) characteristics on Environment, Social, and Governance (ESG) performance in China. The research employed foundational theories such as agency theory, legitimacy theory, stewardship theory, and stakeholder theory. A quantitative approach was adopted, encompassing descriptive statistics and Ordinary Least Squares (OLS) regression. The data was collected from a sample of 100 companies listed on the Shenzhen and Shanghai stock exchanges in China from 2020 to 2023. Secondary data was obtained from the Wind database and the annual reports of the sampled companies. The research findings indicate that AC independence has a positive impact on ESG performance, while AC gender diversity exhibits a negative impact. However, AC meeting frequency and size did not reveal significant effects. This study contributes to enriching the theoretical framework concerning the relationship between ACs and ESG performance, while also addressing existing research gaps. Furthermore, the study provides recommendations for the amendment of China's Company Law.